MALAYSIAN ANIMATED TV SERIES UPIN & IPIN THROUGH PIAGET’S COGNITIVE DEVELOPMENT - Nor ’ Anira Haris (Proceeding IICACS, 2019)
Malaysia‟s animated TV series, Upin & Ipin is one of the biggest names when it comes tothe animation industry. Upin & Ipin‟s ability to attract a large number of local and international fans has inspired an investigation into the internal workings of the elements that contribute to its success. This research aims to identify the content development of the Upin& Ipin series in association with notions of child psychology. By framing Piaget‟s Theory ofCognitive Development, this research explores the development of a child‟s psychology in efforts to formulate animation content best suited for a young viewership. The research identifies with young children below the age of twelve with regards to their preference and interests through observation and questionnaire survey. Furthermore, this research paperdebates Livingstone (2000) who disagrees with Davies‟s (1989) view that television is an important medium for children. Although they use different media in their everyday life, television remains the most popular medium and occupies a significant proportion ofchildren‟s time. And up until 2003, Kaiser Family Foundation has revealed the how‟s andwhy‟s of children watching television. Finally, this research paper has discussed the content and type of stories that psychologically impact and appeal to children.Keywords: Upin & Ipin, Cognitive Development, Children, Jean Piaget